Evaluación de bioactividad de péptidos derivados de la piel de anfibios: enfoque in sílico e in vitro - Ramos Galarza, Jean Pierre (2021)
In this research, we present a computational study of three peptides isolated from the skin secretions of the amphibians Cruziohyla calcarifer and Agalychnis spurelli. Experimentally, the amino acid sequence was elucidated in a previous study by molecular cloning and tandem mass spectrometry. Peptides were coupled with key microbial and carcinogenic receptors by molecular docking. Additionally, molecular dynamics were performed to quantify the receptor-peptide interaction using MMGBSA and MMPBSA. Subsequently, the peptides were synthesized in solid phase and analyzed against the microorganisms E. coli, C. albicans, S. aureus and against three cell lines; A549, HFF and HEK 293T to determine the antimicrobial and anticancer properties. In addition, peptide toxicity was assessed by haemolytic test. Bioinformatic results indicated that AS1 was the most promising because it presented lower bond values in interactions. The MIC trials indicated that AS1 was the only one with antimicrobial activity against the three microorganisms evaluated at a concentration of 256 and 512 mg/L. Although anticancer assays all peptides showed significant p<0.001 to 500 μM activity against the three cell lines, AS1 presented the lowest values. Finally, in the toxicity evaluation the AS1 peptide was the only one that showed toxicity at 256 and 512 mg/L, indicating that it is necessary to look for alternatives to decrease the hemolytic activity. This preliminary study suggests that AS1 was identified as a candidate peptide using bioinformatics tools, allowing a reduction in time and costs.